Increase of sympathetic outflow measured by neuropeptide Y and decrease of the hypothalamic-pituitary-adrenal axis tone in patients with systemic lupus erythematosus and rheumatoid arthritis: another example of uncoupling of response systems. Issue 1 (7th June 2005) - Härle, P; Straub, R H; Wiest, R; Mayer, A; Schölmerich, J; Atzeni, F; Carrabba, M; Cutolo, M; Sarzi-Puttini, P
Abstract : Objective: To study in parallel the outflow of the sympathetic nervous system (SNS) and the hypothalamic-pituitary adrenal (HPA) axis tone in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Methods: 32 patients with SLE, 62 with RA, and 65 healthy subjects (HS) were included. To measure the tone of the HPA axis, plasma ACTH and serum cortisol were determined. Serum neuropeptide Y (NPY) was used to evaluate the sympathetic outflow. Results: Patients with SLE had increased NPY levels in comparison with HS, irrespective of prior prednisolone treatment (p<0.001). For patients with RA, only those with prednisolone treatment had increased NPY levels in comparison with HS (p = 0.016). Daily prednisolone dose correlated positively with serum NPY in RA ( R Rank  = 0.356, p = 0.039). In contrast, plasma ACTH levels were generally decreased significantly in comparison with HS in SLE with prednisolone, and in RA with/without prednisolone. Similarly, serum cortisol levels were also decreased in SLE with/without prednisolone, and in RA with prednisolone. The NPY/ACTH ratio was increased in SLE and RA, irrespective of prior prednisolone treatment. The NPY/cortisol ratio was increased in SLE with/without prednisolone, and in RA with prednisolone. Twelve weeks' anti-TNF antibody treatment with adalimumab did not decrease NPY levels in RA, irrespective of prednisolone treatment. Conclusions: An increased outflow of the SNS was shown and a decreased tone of the HPA axis in patients with SLE and RA. Low levels of cortisol in relation to SNS neurotransmitters may be proinflammatory because cooperative anti-inflammatory coupling of the two endogenous response axes is missing.